Transformasi Pengumpulan Data Kualitatif: Inovasi Aplikasi Mobile untuk Penelitian Kesehatan Masyarakat di Wilayah Terpencil - Elona, Rika Media; Maharani, Vidia Putri; Hartono, Budi; Daud, Valfani Ghutsa (Innovative: Journal Of Social Science Research, 2025)
Transformation in qualitative data collection methods through the use of mobile applications is now an important issue in public health research, especially in remote areas that face various infrastructure and information access constraints. This study aimed to evaluate the effectiveness and challenges of using mobile applications to collect qualitative data in resource-limited settings. This study used qualitative methods with a case study approach, involving 30 participants consisting of health workers, field researchers, and community members from three remote locations. Data were collected through in-depth interviews and participatory observation, and analyzed using thematic analysis to identify key patterns, barriers, and potential uses of mobile apps. The results showed that mobile apps can speed up the data collection process, improve the accuracy and security of information, and facilitate interaction between researchers and respondents. However, the study also found a number of challenges, such as low digital literacy, limited internet network, and resistance to new technology among the community. Overall, the implementation of mobile apps proved to have a positive impact in expanding the reach and efficiency of qualitative data collection in areas with limited access, while encouraging the adoption of technology in public health research. The findings make an important contribution to the development of research methods and offer practical recommendations for policy makers and implementers of health programs in remote areas.